Bowl for modification and cast iron teeming - L. Z. Pisarenko; S. F. Lukashevich; V. K. Filipchik (Литьë и металлургия, 2002)
There is examined the construction of bowl for sphereoidizing processing and pouring of cast iron, allowing to produce castings from VCh from cast iron both of induction smelting and cupola heat.